Mitral valve repair using an autologous pericardial strip in infants and young children. Issue 1 (28th November 2016) - Liu, Li‐Xin; Zhang, Jian‐Feng; Xu, Wei‐Xian; Zhao, Xiao‐Bo; Zhou, Wei‐Li; Xi, Lei; He, Guo‐Wei
Abstract: We have modified the mitral repair technique in infants and small children by using autologous pericardial strips to treat mitral regurgitation resulting from a dilated mitral annulus. Our results demonstrate that this technique maintains stability and flexibility of the mitral annulus and decreases the risk of mitral stenosis.